Metodologia para o ensino de Filosofia: uma proposta de revista digital - Trevisan, Aline Marla De Moura Piau (Universidade Federal de São Carlos, 2025)
The teaching of Philosophy in high school faces significant challenges, such as the devaluation of the subject and the students' detachment from philosophical practice in everyday life. In this context, this study aimed to demonstrate how the practice of teaching Philosophy can be redefined through active methodologies, using digital tools to promote students' critical thinking and autonomy. To achieve this goal, three specific objectives were established: to rescue, strengthen, and develop students' critical thinking through philosophical debates applied to daily life; to implement active methodologies to engage students in the teaching-learning process; and to use digital tools to foster students' autonomy and active participation. This applied research adopted a case study approach with high school classes from a public state school in the interior of São Paulo. The implemented approach aimed to enable student engagement through flipped classroom strategies, the use of digital devices, and the creation of a digital magazine by the students. Data were collected from teachers and students through interviews. The theoretical framework was based on authors such as Dewey (1959; 1979; 2002), who conceives education as a reflective and emancipatory practice; Deleuze (2009), with the creation of new concepts; Gallo (2009; 2012), who views Philosophy as the creation of concepts based on philosophical problems; Prensky (2008; 2010), who discusses the use of ICTs and digital natives in education; Ausubel, Novak and Hanesian (1983), who proposes the theory of meaningful learning; Bacich and Moran (2018), with the creation of an interactive learning environment; and Foucault (1979; 1999), with his analyses of power and knowledge relations in the educational environment. The results indicate that students demonstrated highly satisfactory engagement, with 98% completing the digital magazine. Furthermore, they took on a leading role by presenting the final project to the school community and reported greater involvement and interest in contemporary philosophical issues. It is concluded that the teaching of Philosophy, mediated by active methodologies and digital tools, facilitates meaningful learning and the development of students' critical thinking.
Methodology for teaching Philosophy: a digital magazine proposal
Keywords: Aprendizagem significativa; Filosofia; Tecnologias digitais; Metodologias ativas; CIENCIAS HUMANAS::FILOSOFIA